ANALISIS PENGARUH GEOMETRI FUEL ASSEMBLY TERHADAP KRITIKALITAS DAN DISTRIBUSI FLUKS NEUTRON DALAM TERAS REAKTOR RSG-GAS MENGGUNAKAN OPENMC - Fathan Rastri, Ibnu; Octadamailah, Saga; Sukarman (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The G. A. Siwabessy Multi-Purpose Reactor (RSG–GAS) is included in the MTR type research reactor having a straight plate-shaped fuel element fueled by uranium silicide with a density of 2.96 gU/cm3. This research aims to analyze the influence of the geometry of the straight plate model fuel element on the criticality and distribution of neutron flux in the RSG–GAS reactor core. Monte Carlo simulations with OpenMC were carried out on five types of fuel elements namely from RSG–GAS, HANARO, WWR-SM, MARIA, and BRR, with mass U235 250 grams per fuel element. The research results show that the geometric shapes of different fuel elements influence the criticality value and flux distribution in the same core. The highest criticality value was obtained for the fuel element from HANARO followed by RSG-GAS and the lowest was obtained for the fuel element from WWR-SM. The flux distribution in the fuel elements from MARIA and BRR has a better flux distribution.